2017
DOI: 10.3892/or.2017.5969
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR3 inhibition chemosensitizes lung adenocarcinoma A549 cells in the tumor-associated macrophage microenvironment through upregulation of p53 and PTEN

Abstract: In lung adenocarcinoma, loss of p53 and PTEN in tumors are associated with decreased response to chemotherapy and decreased survival. A means to pharmacologically upregulate p53 and PTEN protein expression could improve the prognosis of patients with p53- and PTEN-deficient tumors. In the present study we revealed that vascular endothelial growth factor receptor 3 (VEGFR3) inhibition in lung adenocarcinoma cells was associated with improved expression levels of both p53 and PTEN in the tumor-associated macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Another study showed that Src modulates LPS-induced local inflammation in colorectal cancer [ 23 ]. Interestingly, several studies have demonstrated that regorafenib reduces pulmonary inflammation by decreasing M1 macrophages and increasing M2 macrophages [ 24 ] and significantly decreases secreted TNF-α, IL-1β, and IL-6 levels in SK-Hep1 cells [ 25 ]. However, whether regorafenib alters LPS-induced proinflammatory cytokine levels in brain glia, including microglia and astrocytes and has protective effects on neuroinflammation-associated neurodegeneration in the brain has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that Src modulates LPS-induced local inflammation in colorectal cancer [ 23 ]. Interestingly, several studies have demonstrated that regorafenib reduces pulmonary inflammation by decreasing M1 macrophages and increasing M2 macrophages [ 24 ] and significantly decreases secreted TNF-α, IL-1β, and IL-6 levels in SK-Hep1 cells [ 25 ]. However, whether regorafenib alters LPS-induced proinflammatory cytokine levels in brain glia, including microglia and astrocytes and has protective effects on neuroinflammation-associated neurodegeneration in the brain has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NK cells isolated from patients with acute myeloid leukemia (AML) were found to express increased levels of VEGFR3 and lower levels of IFN-γ ( Lee et al, 2013 ). Importantly, resident macrophages in lung adenocarcinoma also expressed VEGFR3 and pharmacological inhibition of VEGFR3 signaling sensitized to chemotherapy ( Li et al, 2017 ).…”
Section: The Role Of Tumor Lymphoid Vessels Harboring Endothelial Celmentioning
confidence: 99%
“…VEGFR3 has also been shown to be expressed in neuronal progenitors, osteoblasts, and macrophages [50,51,52]. Furthermore, recent studies have indicated that VEGFR3 expression is detected in different types of cancers and it contributes to tumor progression and lymphatic metastasis (Table 1) [53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93].…”
Section: Regulation Of Vegfr3 Signalingmentioning
confidence: 99%
“…Blockade of VEGFR3 signaling inhibits tumor growth and markedly suppresses the migration and invasion of tumor cells by upregulating the expression of p53 and PTEN. Furthermore, the study’s data revealed that the inhibition of VEGFR3 enhances chemosensitivity of doxorubicin in lung adenocarcinoma cells [58].…”
Section: Clinical Significance Of Vegf-c/vegfr3 Expression In Tumorsmentioning
confidence: 99%